Simulation of an Optical Buffer using Microring Resonator Array with 1.5_m Radius - Suphanchai Punthawanunt; Chat Teeka; Rangson Jomtarak; Preecha P. Yupapin (My University, 2011)
We present the design and FDTD simulations of microring resonator array optical buffer. The proposed buffer consists of six microring array coupled via upper MZI arm, and one microring is coupled via the lower MZI arm, where all coupling gap used is with 105 nm. Results obtained have shown that the delay times of the output signals can be used to form the optical buffer(memory), which can be available for high capacity channel multiplexing and filtering applications.
Keywords: Buffer (optical fiber); Optical buffer; Photonic and Optical Devices